The Bible and African Culture : Mapping Transactional Inroads - Waweru, Humphrey (Book collections on Project MUSE., 2011)
How can African theology survive the self-repetition of mere cultural apologia or contextualization-stereotypes, and mature into a critical theoretical discipline responding to the challenges of the postmodern world-order? Dr. Humphrey M. Wawe contributes here a sound theological reflection using the hitherto unused methodological paradigm of mapping the inroads in the "transaction" between the Bible and African culture